The rate of increase in rating of perceived exertion predicts the duration of exercise to fatigue at a fixed power output in different environmental conditions - Crewe, H.; Tucker, R.; Noakes, T. D. (European Journal of Applied Physiology, 2008)
This study tested the hypothesis that the increase in rating of perceived exertion (RPE) predicts the duration of exercise to exhaustion during exercise in hot conditions. Seven subjects performed five cycling trials in an environmental chamber at temperatures of 15°C (C) and 35°C (H). The cool trials were performed at intensities of 65 and 70% and the hot trials at 55, 60 and 65%. RPE, rectal and skin temperature were measured during trials. Duration to fatigue was significantly shorter in H65 and C70 than H60, C65 and H55 (P < 0.05). RPE rose linearly throughout each trial and the rate of increase in RPE was significantly faster in H65 and C70 than H55 (P < 0.05). There was an inverse linear relationship between trial duration and rate of increase in RPE (r = 0.83). Rectal temperature increased linearly throughout the trial and correlated significantly with RPE (r = 0.92). This study shows that the rate of increase in RPE predicts the duration of exercise to exhaustion at a constant power output in different environmental conditions.